Cayley-type theorems for $g$-dimonoids - Yolchyan, Marlen; Movsisyan, Yuri (Armenian Journal of Mathematics, 2020)
In this paper we prove Cayley-type theorems for $g$-dimonoids using the left (right) acts of sets and concept of dialgebra.